2013
DOI: 10.2147/ott.s53625
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism in the epidermal growth factor gene predicts hepatocellular carcinoma risk in Japanese hepatitis C patients

Abstract: BackgroundA single nucleotide polymorphism (SNP) in the epidermal growth factor (EGF) gene (rs4444903) has been associated with increased risk of cancer, including hepatocellular carcinoma (HCC). The aim of this study was to examine the relationship between the EGF SNP genotype and the development and prognosis of HCC, in a Japanese population.MethodsRestriction fragment-length polymorphism was used to determine the presence of the EGF SNP genotype in 498 patients, including 208 patients with HCC. The level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 34 publications
(51 reference statements)
1
19
0
Order By: Relevance
“…The G allele (A/G and G/G) had higher risk for developing HCC especially in HCV patients when compared with A/A patients. 20 But they could not explain why HCC was higher in patients with A/G genotype when compared with the G/G genotype; however, this has been observed occasionally, in other studies [13,21,22] .…”
Section: Resultsmentioning
confidence: 89%
“…The G allele (A/G and G/G) had higher risk for developing HCC especially in HCV patients when compared with A/A patients. 20 But they could not explain why HCC was higher in patients with A/G genotype when compared with the G/G genotype; however, this has been observed occasionally, in other studies [13,21,22] .…”
Section: Resultsmentioning
confidence: 89%
“…The EGF gene encodes epidermal growth factor. All studies found a significant association with the outcome, although for one, the association was only significant for the A/A to A/G comparison (and not for A/A to G/G). Additionally, a meta‐analysis describing comparisons between HCC patients and both patients with liver disease and healthy controls found a significant overall effect.…”
Section: Resultsmentioning
confidence: 93%
“…Three original studies were identified investigating the rs4444903 SNP of the EGF gene, two studying HCC(578 patients in total) and one studying fibrosis, with a variety of comparison groups (including HCV‐infected and HCV‐related cirrhosis patients). The EGF gene encodes epidermal growth factor.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies including meta-analyses have shown relationships between SNPs and human cancer susceptibility [21][22][23][24][25]. For these SNPs to be useful biomarkers, they should be validated in several populations because of racial differences [26]. However, the clinical significance of CD44 SNPs has not been thoroughly established, especially in patients with gastric cancer [8,11,[27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%